FAMILY SOCIAL CAPITAL ASSOCIATION WITH LEARNING OUTCOMES OF STUDENTS IN NNAMDI AZIKIWE UNIVERSITY HIGH SCHOOL, AWKA-NIGERIA (Journal of Guidance and Counselling Studies, 2023)
Family involvement in education can make an impressive difference in learning outcomes. This study therefore examined family social capital association with learning outcomes of students in Nnamdi Azikiwe University high school, Awka. Three research questions and three null hypotheses tested at 0.05 significance level guided the study. The correlation research design was employed for the study. The population of the study comprised 80 (SS3) students of 2021/2022 academic session.No sampling was done because the population is small.Two sets of instruments were used for the study namely: A researcher-developed instrument titled “Family Social Capital and Learning Outcomes” (FSCLO) and students achievement scores in WAEC and NECO examinations. Reliability of the researcher-developed instrument was established using Cronbach alpha and an internal coefficient of 0.78 was obtained. The data were analyzed using correlation for the research questions and t-test for correlation significance for the hypotheses. The results showed a positive and significant association between family social capital and learning outcomes of students in Nnamdi Azikiwe University High School, Awka.Based on the findings of the study, it was recommended that parents should as much as possible render the much support within their capacity to their children, monitor and supervise their children’s academic activities for positive learning outcomes.
Keywords: Family; Social capital; Students; Learning outcomes